Mechanical Evaluation of an Orthogonal Angle-Stable Interlocking Nail in a Comminuted Fracture Model - Lucena, Dayvid V.F.; Minto, Bruno W.; Rocha, Thiago A.S.S.; Malta, Caio A.S.; Carrera, Alefe L.C.; Ferreira, Danyelle R.C.; Galíndez, Júlian A.S.; Dias, Luis G.G.G. (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
This study aimed to describe an orthogonal angle-stable (ASO) intramedullary nail, evaluate its mechanical properties, and compare its performance with a conventional and an angle-stable nails.Synthetic diaphyseal models with a 25-mm gap fracture were 3D printed using polylactic acid. The ASO nail, fabricated from 316 L stainless steel, featured two orthogonal distal holes spaced 5.5-mm apart. Mechanical properties were evaluated through axial compression and torsion tests until failure. The stiffness and yield load under axial compression and peak torque under torsion were used to compare the ASO nail (ASO group) with a conventional interlocking (IC group) and a uniplanar angle-stable (ASU group) nails. Seven tests per group were performed and analysed using Kruskal–Wallis and Dunn's post hoc tests.The ASO and ASU nails exhibited similar stiffness under axial loading and demonstrated greater stiffness than the IC nails. No differences were observed among the groups regarding yield load or peak torque under torsion.The ASO nail exhibited biomechanical properties similar to the ASU nail and both demonstrated superiority over the IC. Further studies focusing on implant development and refinement of the implantation technique are necessary before clinical application can be considered.
Keywords: dog; interlocking nail; fracture; orthogonal; angle-stable